Which Types of Family are at Risk of Food Poverty in the UK? A Relative Deprivation Approach. Issue 1 (5th January 2019) - O'Connell, Rebecca; Owen, Charlie; Padley, Matt; Simon, Antonia; Brannen, Julia
Abstract : Not enough is known in the UK about how economic phenomena and policy changes have impacted families' ability to feed themselves. This article employs a novel way of identifying the types of UK families at risk of food poverty over time. Applying a relative deprivation approach, it asks what counts in the UK as a socially acceptable diet that meets needs for health and social participation and how much this costs. Comparing this to actual food expenditure by different family types, between 2005 and 2013, it identifies which are spending less than expected and may be at risk of food poverty. The analysis finds the proportion has increased over time for most family types and for lone parents and large families in particular. The discussion considers findings in light of changing economic and policy contexts and the implications for policy responses of how food poverty is defined and measured.